Properties of hydroxyapatite/zirconium oxide nanocomposites - Winatsara Kantana (2018)
Effects of zirconium oxide (ZrO2) nanoparticles additive on the microstructure and physical properties of hydroxyapatite (HA) were investigated. The HA powder was derived from natural bovine bone by a sequence of thermal processes. The composites containing nanoparticles of ZrO2(0.2-1.0 vol%) were fabricated by a solid-state reaction mixed oxide method. All samples showed traces of HA, beta-tricalcium phosphate (β-TCP) and alpha-tricalcium phosphate (α-TCP) phases while the x≥0.1 samples also showed ZrO2phase. Amount of β-TCP and α-TCP phases tend to decrease with ZrO2. The additive inhibited grain growth as a result of a decrease in grain size. However, the x=0.2 sample exhibited higher hardness value which is consistent with the density data. In addition, bioactivity test suggested that the additive promoted an apatite forming with the values of Ca/P close to the value obtained from HA. © 2013 Elsevier Ltd and Techna Group S.r.l.